The nuts & bolts of grant writing - Carr, Cynthia E. (Los Angeles : SAGE, 2015)
In this practical, accessible guide, author Cynthia Carr shares her expertise in writing and winning grants. Written for students, faculty, and university personnel, she shares her best practices for planning, writing, and winning research grants. Complete with embedded examples from a variety of disciplines, this guide offers novices the tools they need to begin writing grants and allows those with more experience to sharpen their skills. --Publisher's description.
Includes bibliographical references (pages 217-218) and index.
Keywords: Proposal writing in research -- United States; Proposal writing for grants -- United States; Proposal writing in education -- United States